Effects of sulfadiazine and Cu on soil potential nitrification and ammonia-oxidizing archaea and bacteria communities across different soils - Hou, Guoqin; Wazir, Zafran Gul; Liu, Jing; Wang, Guizhen; Rong, Fangxu; Xu, Yuzhi; Li, Mingyue; Liu, Kai; Liu, Aijv; Liu, Hongliang; Wang, Fayuan (Frontiers in Microbiology, 2023)
Sulfadiazine (SDZ) and copper (Cu) are frequently detected in agricultural soils, but little is known on their single or combined impact on ammonia oxidizing microbial community and function across different soils. In this study, a microcosm was conducted to distinguish the microbial ecotoxicity of SDZ and Cu across different soils by analyzing soil potential nitrification rate (PNR) and the amoA gene sequences. The results showed that the single spiking of SDZ caused a consistent decrease of soil PNR among three tested soils, but no consistent synergistic inhibition of SDZ and Cu was observed across these soils. Moreover, across three tested soils, ammonia oxidizing microorganisms showed diverse responses to the single or joint exposure of SDZ and Cu at amoA gene abundance, and diversity as well as the identified genus taxa of ammonia-oxidizing archaea (AOA) and bacteria (AOB). Meanwhile, only the specific genus taxa of AOA or AOB consistently corresponded to the variation of soil PNR across different treated soils. The further principal component analysis (PCA) exhibited that the variable influence of SDZ and Cu on ammonia oxidizing microbial community and function was greatly dependent on soil type. Therefore, to correctly evaluated the ecotoxicity of soil contamination, the difference caused by soil types should be given more attention in addition to a full-scale analysis from ecological functionality to a specific soil prokaryotic taxon. This study proposes an integrative assessment of soil properties and multiple microbial targets to soil contamination management.